HUBUNGAN PENDIDIKAN DAN PEKERJAAN DENGAN PEMILIHAN ALAT KONTRASEPSI DALAM RAHIM DI RB MITRA ANANDA PALEMBANG - Rini Anggeriani Rini Anggeriani (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2015)
According to data from World Health Organitation said The participants are active contraceptive, the use of condoms (80-90%), Pill (90-96%), Injectable (95-97%), Implant (97-99%), Intrauterine Devices (94-99%), Vasectomi (00.4%-99,8%), Tubectomi (99,5-99,9%) (Kusmaningrum, 2009). To determine the relitonship of education and employment with the Selection of an Intrauterine Device at Mitra Ananda’s Clinic Year 2015. The research methodology using analitic survey is survey research for explain something by cross sectional approach. Data using are Secondary data and taken through led interview using Checklist. . The population on of this research are 430 participants active contraceptive, the sample are 80 participants active contraceptive. They are choosen by random sampling technique. Analysis using statistic chi-square. The Result from 80 respondents who choose intrauterine devices as many as 50 Respondents (62,5%), The respondent of highly educated is 57 respondents (57%) and the respondet of worked is 47 respondent (58,8%). The result of bivariat analysis by chi-square statistic test shown that there’s relationship education with the selection of an intrauterine device where p value 0,013<0,1 and there’s relationship of employment with the selection of an intrauterine device where p value 0.004<0,1. There is significant relationship between education and employment with the selection of an intrauterine device at Mitra Ananda’s Clinic Year 2015. Menurut data dari WHO (World Health Organitation) mengatakan peserta-peserta aktif kontrasepsi yaitu pemakaian kondom (80%-90%), Pil (90%-96%), Suntik (95%-97%), Susuk (97%-99%), IUD (94%-95%), Vasektomi (99,4%-99,8%), Tubektomi (99,5%-99,9%) (Kusmaningrum, 2009). Untuk mengetahui Hubungan Pendidikan dan Pekerjaan Dengan Pemilihan Alat Kontrasepsi Dalam Rahim di Rumah Bersalin Mitra Ananda Palembang Tahun 2015?. Jenis penelitian yang digunakan adalah survey analitik yaitu penelitian survey yang diarahkan untuk menjelaskan suatu keadaan atau situasi dengan pendekatan Cross Sectional. Data yang digunakan adalah data Sekunder dengan alat ukur Checklist. Populasi dalam penelitian ini adalah semua Akseptor KB 430 orang, sampel penelitian ini adalah Sebagian Akseptor KB 80 orang, teknik yang digunakan Random Sampling Analisa data dengan menggunakan hasil uji statistik Chi-Square. Dari 80 responden, yang memilih Alat Kontrasepsi Dalam Rahim sebanyak 50 responden (62,5%) dan yang berpendidikan tinggi sebanyak 57 responden (57%), yang bekerja sebanyak 47 Responden (58.8%). Hasil analisa bivariat dengan uji statistik chi-square menunjukan bahwa ada hubungan yang bermakna antara pendidikan dengan pemilihan Alat Kontrasepsi Dalam Rahim dimana p value 0,013<0,1 dan ada hubungan bermakna antara pekerjaan dengan pemilihan Alat Kontrasepsi Dalam Rahim dimana p value 0,004<0,1. Terdapat hubungan yang bermakna antara Pendidikan dan Pekerjaan Dengan Pemilihan Alat Kontrasepsi Dalam Rahim di Rumah Bersalin Mitra Ananda Palembang Tahun 2015.